Decomposing mechanisms of abnormal saccade generation in schizophrenia patients: Contributions of volitional initiation, motor preparation, and fixation release. (23rd July 2016) - Reuter, Benedikt; Elsner, Björn; Möllers, David; Kathmann, Norbert
Abstract: Clinical and theoretical models suggest deficient volitional initiation of action in schizophrenia patients. Recent research provided an experimental model of testing this assumption using saccade tasks. However, inconsistent findings necessitate a specification of conditions on which the deficit may occur. The present study sought to detect mechanisms that may contribute to poor performance. Sixteen schizophrenia patients and 16 healthy control participants performed visually guided and two types of volitional saccade tasks. All tasks varied as to whether the initial fixation stimulus disappeared (fixation stimulus offset) or continued during saccade initiation, and whether a direction cue allowed motor preparation of the specific saccade. Saccade latencies of the two groups were differentially affected by task type, fixation stimulus offset, and cueing, suggesting abnormal volitional saccade generation, fixation release, and motor preparation in schizophrenia. However, substantial performance deficits may only occur if all affected processes are required in a task.